Anatase-rutile phase transformation and photocatalysis in peroxide gel route prepared TiO2 nanocrystals: Role of defect states - Anitha, B.; Khadar, M. Abdul (Solid state sciences, 2020)
Peroxide gel method, utilizing titanyl sulfate as a titanium source, is employed to synthesize TiO2 nanocrystals. The nanoparticles are further annealed at different temperatures of 300, 500, 700, and 900 °C. XRD analysis reveals a phase pure anatase structure for the as-prepared sample and anatase-rutile mixed-phase for annealed TiO2 nanocrystals. UV–visible diffuse reflectance and Fourier transform infrared spectroscopic measurements also confirm the formation of anatase-rutile mixed phase for annealed samples. Micro-Raman spectra recorded for three different excitation wavelengths suggest the formation of rutile phase in the interior of the anatase nanoparticles upon annealing. Photocatalytic efficiencies of the TiO2 nanocrystals are evaluated by choosing methyl orange as a model dye under UV and simulated solar irradiations. Presence of defect states, mainly oxygen vacancies, that form subband states extending from shallow to the deep levels in TiO2 bandgap are confirmed from photoluminescence measurements. Among the TiO2 samples, the nanocrystals annealed at 300 °C shows the maximum photocatalytic activity. The observed variation in the photocatalytic activities of the TiO2 nanocrystals is explained as per the difference in the intensity ratio of the emission peaks corresponding to those of shallow and deep traps in the bandgap of the TiO2 nanocrystals. [Display omitted] •Synthesis of TiO2 nanocrystals by peroxide gel method using titanyl sulfate.•Anatase-rutile phase transformation at a relatively lower temperature of 300 °C.•Nucleation of rutile phase in the interior of anatase TiO2 nanocrystals.•Correlation between PL emission and photocatalytic activity of the nanocrystals.